2017
DOI: 10.1093/ofid/ofx163.810
|View full text |Cite
|
Sign up to set email alerts
|

Injection Drug Use and Infectious Disease Practice: A National Provider Survey

Abstract: BackgroundThe opioid epidemic has swept across the U.S. at a staggering rate, with an estimated half million to one million persons injecting drugs annually. Rates of hospitalization for injection drug use (IDU)-related infection have risen precipitously, comprising an escalating proportion of infectious diseases provider volume in highly impacted regions.MethodsIn March 2017, the Emerging Infections Network surveyed their national network of infectious diseases (ID) physicians to evaluate perspectives relatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…When surveyed about the safety of OPAT for PWID, opinions among clinicians were mixed. Just over half of the respondents (56%) agreed with the following statement: “It is less safe and successful than non-IVDUs but benefits outweigh risks.” Conversely, only 16.0% of clinicians agreed with the statement “It is not safe and the whole system concerns me.” In a survey study of 672 ID physicians in the United States, confidence and acceptance of OPAT for PWID were found to be low, despite a high frequency of caring for patients with infections related to IDU [ 9 , 26 ]. Of those surveyed, 88% reported caring for at least 1 patient with IDU-related infections every month, but few indicated that they would provide OPAT for PWID.…”
Section: Discussionmentioning
confidence: 99%
“…When surveyed about the safety of OPAT for PWID, opinions among clinicians were mixed. Just over half of the respondents (56%) agreed with the following statement: “It is less safe and successful than non-IVDUs but benefits outweigh risks.” Conversely, only 16.0% of clinicians agreed with the statement “It is not safe and the whole system concerns me.” In a survey study of 672 ID physicians in the United States, confidence and acceptance of OPAT for PWID were found to be low, despite a high frequency of caring for patients with infections related to IDU [ 9 , 26 ]. Of those surveyed, 88% reported caring for at least 1 patient with IDU-related infections every month, but few indicated that they would provide OPAT for PWID.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, clinicians' concerns regarding the misuse of a peripherally inserted central catheter to inject drugs in addition to treatment nonadherence, unstable living situations, and stigma associated with substance use have typically excluded people who inject drugs from receiving OPAT. 16,17 Despite these concerns, a 2018 systematic review 8 found that OPAT may be safe and beneficial for treating IDU-IE. To our knowledge, no study to date has compared the long-term impact and cost-effectiveness of OPAT with IV and partial oral antibiotic treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy, OPAT, is widely used to treat infections that require prolonged antibiotic therapy, and this treatment strategy has a proven safety record . However, clinicians’ concerns regarding the misuse of a peripherally inserted central catheter to inject drugs in addition to treatment nonadherence, unstable living situations, and stigma associated with substance use have typically excluded people who inject drugs from receiving OPAT . Despite these concerns, a 2018 systematic review found that OPAT may be safe and beneficial for treating IDU-IE.…”
Section: Introductionmentioning
confidence: 99%